CUPID, the Cuore upgrade with particle identification - CUPID Collaboration (European Physical Journal C: Particles and Fields)
Abstract CUPID, the CUORE Upgrade with Particle Identification, is a next-generation experiment to search for neutrinoless double beta decay ( $$0ν β β $$ 0 ν β β ) and other rare events using enriched Li $$_{2}$$ 2 $$^{100}$$ 100 MoO $$_{4}$$ 4 scintillating bolometers. It will be hosted by the CUORE cryostat located at the Laboratori Nazionali del Gran Sasso in Italy. The main physics goal of CUPID is to search for $$0ν β β $$ 0 ν β β of $$^{100}$$ 100 Mo with a discovery sensitivity covering the full neutrino mass regime in the inverted ordering scenario, as well as the portion of the normal ordering regime with lightest neutrino mass larger than 10 meV. With a conservative background index of 10 $$^{-4}$$ - 4 cts $$/($$ / ( keV $$· $$ · kg $$· $$ · yr $$)$$ ) , 240 kg isotope mass, 5 keV FWHM energy resolution at 3 MeV and 10 live-years of data taking, CUPID will have a 90% C.L. half-life exclusion sensitivity of $$1.8· 10^{27}$$ 1.8 · 10 27 yr, corresponding to an effective Majorana neutrino mass ( $$m_{β β }$$ m β β ) sensitivity of 9–15 meV, and a $$3σ $$ 3 σ discovery sensitivity of $$1· 10^{27}$$ 1 · 10 27 yr, corresponding to an $$m_{β β }$$ m β β range of 12–21 meV.